2022
DOI: 10.3389/fendo.2022.983792
|View full text |Cite
|
Sign up to set email alerts
|

The effect of early life events on glucose levels in first-episode psychosis

Abstract: First episode of psychosis (FEP) patients display a wide variety of metabolic disturbances at onset, which might underlie these patients’ increased morbidity and early mortality. Glycemic abnormalities have been previously related to pharmacological agents; however, recent research highlights the impact of early life events. Birth weight (BW), an indirect marker of the fetal environment, has been related to glucose abnormalities in the general population over time. We aim to evaluate if BW correlates with gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Those patients affected by intrauterine stressful events are prone to develop metabolic abnormalities at earlier stages and so present reduced life-expectancy (Barker et al, 1989;Garcia-Rizo and Bitanihirwe, 2020;Kirkpatrick et al, 2008). Current literature highlights the impact of OCs in the metabolic (Garcia-Rizo et al, 2022;García-Rizo et al, 2020;Garriga et al, 2019a), cognitive (Amoretti et al, 2022), psychopathological (Mezquida et al, 2021;Sagué-Vilavella et al, 2022;Verdolini et al, 2023) and neurostructural (Costas-Carrera et al, 2020) outcome of patients with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Those patients affected by intrauterine stressful events are prone to develop metabolic abnormalities at earlier stages and so present reduced life-expectancy (Barker et al, 1989;Garcia-Rizo and Bitanihirwe, 2020;Kirkpatrick et al, 2008). Current literature highlights the impact of OCs in the metabolic (Garcia-Rizo et al, 2022;García-Rizo et al, 2020;Garriga et al, 2019a), cognitive (Amoretti et al, 2022), psychopathological (Mezquida et al, 2021;Sagué-Vilavella et al, 2022;Verdolini et al, 2023) and neurostructural (Costas-Carrera et al, 2020) outcome of patients with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…This model suggests that "undesirable conditions" during the perinatal period can have long-lasting metabolic consequences. Indeed, recent research showed that birth weight (BW), an indirect measure of the intrauterine milieu, is related to weight gain Garriga et al, 2019a) and glucose values in FEP (Garcia-Rizo et al, 2022), with T2DM in schizophrenia (Fernandez-Egea et al, 2020) and in affective disorders (Garriga et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%